1987
DOI: 10.1121/1.2024178
|View full text |Cite
|
Sign up to set email alerts
|

Auditory word recognition is not more sensitive to word-initial than to word-final stimulus information

Abstract: Auditory word recognition is not more sensitive to word-initial than to word-final stimulus information M. J. van der Vlugt, and S. G. Nooteboom

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…In both native and non-native listening, the masking of word-initial information is more detrimental to spoken-word recognition than the masking of word-final information. So, in line with previous studies [1][2][3][4][5][6][7], word-initial information is more important for successful word recognition than word-final information. Moreover, as expected, fewer words are recognized when listening conditions deteriorate (in line with, e.g., [15]).…”
Section: General Discussion and Conclusionsupporting
confidence: 74%
See 1 more Smart Citation
“…In both native and non-native listening, the masking of word-initial information is more detrimental to spoken-word recognition than the masking of word-final information. So, in line with previous studies [1][2][3][4][5][6][7], word-initial information is more important for successful word recognition than word-final information. Moreover, as expected, fewer words are recognized when listening conditions deteriorate (in line with, e.g., [15]).…”
Section: General Discussion and Conclusionsupporting
confidence: 74%
“…Although listeners use both word-initial and word-final information for candidate word selection and recognition [1][2][3], word-initial information seems to be more important in evaluating lexical candidates than word-final information, at least in clean listening conditions [1] [4]. In the presence of background noise, however, native listeners have been found to adapt the activations of candidate words during competition [4] [5] so that offset competitors are activated relatively more compared to clean listening conditions [4] [6].…”
Section: Introductionmentioning
confidence: 99%
“…An increased probability of correct identification with increasing word-onset information, thus, might not necessarily imply that the analysis is sequential, but that the word is simply better specified. Van der Vlugt and Nooteboom (1986) suggested that in word recognition, all parts of a spoken word can be used effectively, so long as proper alignment with word candidates is ensured, a task ordinarily more efficient when the information available pertains to a word's onset.…”
Section: Discussionmentioning
confidence: 99%
“…There is substantial evidence that listeners are able to exploit 19 whatever information is on offer -for instance, that they can extract useful information from the ends of words if they did not hear the beginnings because of noise interference. Van der Vlugt and Nooteboom (1986) found that beginnings and ends of synthesised words were equally effective prompts for correct recognition responses when the rest of the word was masked with noise. Slowiaczek et al (1987) Native listener adjustment to noise is in fact very sensitive, and also accords with our understanding of the spoken-word recognition process.…”
Section: The Effects Of Adverse Conditions On Spoken-word Recognitionmentioning
confidence: 96%